2021
DOI: 10.3390/ijms22157928
|View full text |Cite
|
Sign up to set email alerts
|

A Fork Trap in the Chromosomal Termination Area Is Highly Conserved across All Escherichia coli Phylogenetic Groups

Abstract: Termination of DNA replication, the final stage of genome duplication, is surprisingly complex, and failures to bring DNA synthesis to an accurate conclusion can impact genome stability and cell viability. In Escherichia coli, termination takes place in a specialised termination area opposite the origin. A ‘replication fork trap’ is formed by unidirectional fork barriers via the binding of Tus protein to genomic ter sites. Such a fork trap system is found in some bacterial species, but it appears not to be a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…16 The results revealed that the host cell viability (in respect of growth rate and cellular morphology) and stability of genome structure were not influenced by the topological changes when the linearization of the chromosome was designed at the region apart from the bacterial ori site. 16 This is in agreement with a later report which found that an E. coli chromosome linearized by TelN at a tos sequence inserted near the chromosome dimer resolution site dif (located within terminus region of the chromosome 72 ) does not delay the growth rate of wild-type E. coli. 73 Surprisingly, linearization of the circular E. coli chromosome almost did not alter the genome-wide gene expression, as only three genes were found to exhibit different gene expression levels among the 4300 genes analyzed.…”
Section: Adaptation Of Teln-tos For the Genetic Studies Of Bacterial ...supporting
confidence: 91%
“…16 The results revealed that the host cell viability (in respect of growth rate and cellular morphology) and stability of genome structure were not influenced by the topological changes when the linearization of the chromosome was designed at the region apart from the bacterial ori site. 16 This is in agreement with a later report which found that an E. coli chromosome linearized by TelN at a tos sequence inserted near the chromosome dimer resolution site dif (located within terminus region of the chromosome 72 ) does not delay the growth rate of wild-type E. coli. 73 Surprisingly, linearization of the circular E. coli chromosome almost did not alter the genome-wide gene expression, as only three genes were found to exhibit different gene expression levels among the 4300 genes analyzed.…”
Section: Adaptation Of Teln-tos For the Genetic Studies Of Bacterial ...supporting
confidence: 91%
“…However, it now appears that the type II replication fork trap, which is mostly found in Enterobacteriaceae, is more of an exception or even an anomaly with respect to its many redundant Ter sites and their wide spread around the chromosome. It seems that the complexity of the type II fork trap in E. coli and closely related species [46] has merely distracted scientists from capturing the elegance and simplicity of the type I system in other Enterobacterales. Nevertheless, the work on the E. coli Tus-Ter complex was instrumental to decipher the unique Tus-Ter-lock mechanism [9], which still stands true and is seemingly conserved in all tus-harbouring bacteria.…”
Section: The Ancestral Type I Dna Replication Fork Trapmentioning
confidence: 99%
“…The highly conserved ter core (6, 8–18) is highlighted by a darker grey. Tus binding ( Toft et al, 2021 ), in vivo fork blocking observed by 2D gel electrophoresis ( Duggin and Bell, 2009 ) and analysis whether a ter site is part of an open reading frame ( Duggin and Bell, 2009 ; Goodall et al, 2021 ) are indicated (see text for further details).…”
Section: Introductionmentioning
confidence: 99%
“…However, within the limits of this resolution, our data demonstrate that the fork fusion point, as determined by LOESS regression, is in precisely the same location in the presence and absence of Tus protein ( Rudolph et al, 2013 ; Dimude et al, 2016 ). The only change observed is a mild distortion of the marker frequencies in the vicinity of the fusion point (see Dimude et al (2016) and Goodall et al (2021) for a direct comparison of the replication profiles in the presence and absence of Tus terminator proteins). In contrast, in cells in which the replichore arrangement is artificially skewed by an additional ectopic origin, the fork fusion point is significantly shifted if the tus gene is deleted, as expected ( Ivanova et al, 2015 ; Dimude et al, 2018b ; Syeda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation